What works : vie Verhaltensdesign die Gleichstellung revolutionieren kann. - Bohnet, Iris (C.H. Beck, 2017)
Gender equality is a moral and a business imperative. But unconscious bias holds us back and de-biasing minds has proven to be difficult and expensive. Behavioral design offers a new solution. Iris Bohnet shows that by de-biasing organizations instead of individuals, we can make smart changes that have big impacts--often at low cost and high speed.